Flux density and power loss distribution in 100kVA Distribution Transformer core assembled with different cutting angle of T-joint - Shuhaimi, Zakaria@Abdullah (Universiti Malaysia Perlis (UniMAP), 2010)
The power losses occurring under magnetising condition have received a great deal of attention for a long time. The transformer designs with Butt Lap joint cause the highest power loss at the T-joint. These due to the flux need to rotate 90º into the hard direction and transfer up and down to the adjacent layers causes high rotational power loss occurred at the T-joint. To overcome this problem, the different cutting angle such as 23º, 45 º and 60º at the T-joint was introduces in order to find out the most efficient design. The development of the 100kVA Distribution Transformer model core with the four difference types of the T-joint for the power loss and building factor measurement has been tested in order to find which T-joint has minimum power loss and better building factor. The localised flux density was measured using the search coil in order to find out their distribution at the corner joint and T-joint. The fundamental, third and fifth harmonic in the normal and inplane flux density were measured at the corner joint and T-joint. The localised power loss was measured using the thermistor at the similar location of the search coil. The results show that the minimum power loss, better building factor, the minimum fundamental, third and fifth harmonic the normal and inplane flux density and also minimum localised power loss are occurred at the transformer model core assembled with the 60° T-joint.